2018
DOI: 10.1016/bs.acr.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of MDA-7/IL-24 a Multifunction Protein in Human Diseases

Abstract: Subtraction hybridization identified genes displaying differential expression as metastatic human melanoma cells terminally differentiated and lost tumorigenic properties by treatment with recombinant fibroblast interferon and mezerein. This approach permitted cloning of multiple genes displaying enhanced expression when melanoma cells terminally differentiated, called melanoma differentiation associated (mda) genes. One mda gene, mda-7, has risen to the top of the list based on its relevance to cancer and now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 165 publications
3
65
0
Order By: Relevance
“…Many cytokines, such as IL-24 and IL-37, exert tumorsuppressing effects and related clinical trials of tumor treatment have been conducted. 15,18 In our article, we demonstrated that both recombinant CYTL1 and overexpression of CYTL1 could inhibit the migration of multiple types of tumor cells. It is possible that the tumorsuppressing cytokine CYTL1 might be used in tumor treatment, such as lung cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Many cytokines, such as IL-24 and IL-37, exert tumorsuppressing effects and related clinical trials of tumor treatment have been conducted. 15,18 In our article, we demonstrated that both recombinant CYTL1 and overexpression of CYTL1 could inhibit the migration of multiple types of tumor cells. It is possible that the tumorsuppressing cytokine CYTL1 might be used in tumor treatment, such as lung cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, IL-24 has been proven to suppress multiple signaling pathways in various human cancer cells, such as melanoma, cervical cancer, lung cancer and prostate cancer, 13 and this suppressive effect leads to tumor cell death and the inhibition of tumor angiogenesis and metastasis. 14,15 Because recombinant IL-24 shows selective cytotoxicity against cancer cells, clinical trials have investigated the use of IL-24 for the treatment of solid tumors. 16,17 Another example is IL-37, whose intracellular mature form markedly inhibits the migration of multiple types of tumor cells by inhibiting Rac1 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Low concentration of IL-24 promotes inflammatory cytokine expression, leading to the proinflammatory response. In contrast, high concentration of IL-24 strongly induces apoptosis of cancer cells (12,14). IL-24 expression was remarkably correlated with histological differentiation, but inversely correlated with the degree of lymph node involvement in rectal cancer (15), which played an important anti-tumor role for colon cancer therapy (16,17) and even reversed multidrug resistance to chemotherapy in human colorectal cancer cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…6 IL-24 is also implicated in autoimmune diseases such as inflammatory bowel disease and rheumatoid arthritis. 7 In light of the identification of IL24-directed IgE in CSU, we wondered whether local IL-24 is produced during the urticarial reaction.…”
Section: Increased Expression Of Il-24 In Chronic Spontaneous Urticariamentioning
confidence: 99%